Penerapan Model Dick And Carey Berbasis Progresivisme Untuk Meningkatkan Efektivitas Pembelajaran PAI Di SMA Muhammadiyah 1 Ponorogo - Anas Fiqru Rosidin (https://ejournal.insuriponorogo.ac.id/, 2024)
This research aims to analyze the application of the progressivism-based Dick and Carey model in increasing the effectiveness of Islamic Religious Education (PAI) learning at SMA Muhammadiyah 1 Ponorogo. This research focuses on the steps in implementing the learning model, including communicating learning objectives based on Islamic values, analysis of student characteristics, project-based development strategies or group discussions, as well as implementation and evaluation of learning based on creative assignments. Apart from that, this research also identified supporting factors, such as teacher competence, school facilities, and curriculum support, as well as inhibiting factors such as time constraints, teachers' lack of understanding of progressivism, and student resistance to new methods. The research method used is a qualitative approach using interview techniques, observation and document analysis. The research results show that although there are several challenges, implementing this model can increase the effectiveness of PAI learning by strengthening students' character and critical thinking skills.